Construções do imaginário em João Manuel Simões - Costa, Sueli Aparecida da (2007)
The objective of this study is to investigate the constructions of an imaginary and poetic universe by João Manuel Simões, Brazilian poet, from the state of Paraná, was born in Mortágua Portugal and definitely settled down in Curitiba. The research embodies images and subjects in which is possible to notice, with more evidence, the relation between poetry and the imaginary, such as the dream, the inspiration, the imagination, the word and the silence, the childhood, the memory, the time, the bird, the duplicity and the mirror. In spite of not being a well known poet in academic means, he is recognized by Brazilian critics. He has a vast production, involving literary critic, essay, prose and poetry. The research of bibliography is related with authors that deal with the imaginary and poetry subjects, such as Gaston Bachelard, Gilbert Durand, Philippe Malrieu, Claude-Gilbert Dubois, Claude Esteban, Mikel Dufrenne, Percey B. Shelley, Paul Valéry, Octavio Paz, Alfredo Bosi and others. The paper is composed of four chapters, in each one of them, we look for an intersection between the theoretical reference and the analysis of the poems from the subjects of the research in the Simões poetical work. In the first chapter, the chosen subject is referring to the association between the poetic universe and the imaginary one, especially when what concerns is the presentation of the poetry as belonging to the world of imagination and dream. The second chapter points out the images of the bird, the time, and the mirror and duplicity, images that appear with more frequency in the simonian lyric. In the third chapter an analysis of the strong relation between the word and the silence in the plot of the poetic construction. In the fourth and last chapter, stands out the poetry-memory-imagination that is related just when deals with childhood images and memories. From the poetical making to the images and symbols, the research intends to investigate the constructions of the imaginary and the poet s poetical constructions showing the intrinsic relation between the poetry and the imaginary.